NU DALAM PERKEMBANGAN PEMIKIRAN PENDIDIKAN ISLAM - Moh. Nafi’ (STAI Ma'had Aly Al-Hikam Malang, 2012)
In the year 1980, NU was growing in new enthusiasm in education development and intellectual tradition of Islam and also various effort improve; repair social and economy of NU followers, especially who live in the village. In this year NU also develops the effort of religious discourse in development. The basic reason of this effort for NU is meant to hold firmness one of the four madzhab ( Maliki, Hanafi, Syafi’i, and Hambali) , but not rarely NU people who like to use ijtihad as one of the way of to comprehend Islam openly and is lenient. Religious pattern in this wide of NU. NU which initially follow Asy’ari and Maturidi in the field of tauhid, Imam Junaid Al Baghdadi in tasawuf, by degrees all various a new wrinkle able to relevant between Ahlusunnah Wal Jamaah with plurality of life believe in existing reality. In facing social change, NU have owned motto: “ Maintain good old value and look for better new value”. With this motto NU seems in thinking of education in Indonesia go trough strategic position. Through activity conducted by NU during the time, NU have given contribution which enough mean to growth idea of education in Indonesia. It can be witnessed shifting of understanding of Islam having the character of textual become contextual. So that by conducting integral view can be change religious view of Indonesian nation have the character of incluusive one